Effects of Duration of Breastfeeding During Infancy on Vascular Dysfunction in Adolescents - Sukman Tulus Putra; Muchtaruddin Mansyur; Sudigdo Satroasmoro (Acta Medica Indonesiana)
Aim: to investigate the effect of breastfeeding duration on vascular characteristics in adolescence. Methods: we conducted a retrospective cohort study on adolescents aged 15-18 years old. Breastfeeding duration was inquired using a questionnaire filled by parents and categorized into 0-<2, 2-<4, 4-<6, 6-<12, and >12 months. Outcomes assessed were flow mediated dilation (FMD), carotid intima media thickness (CIMT), anthropometrics. Analysis was done using linear regression and MANOVA general linear model with cardiovascular risk factors as the dependent variables and breastfeeding duration as the independent variable with further adjustment for confounders. Results: 285 subjects aged 15-18 years were enrolled. Breastfeeding duration of 4-<6 months was associated with thinner CIMT and the effect was more prominent after adjustment for gender and postnatal tobacco exposure (mean difference=24.28 micrometer, p=0.045). No statistically significant association was found with FMD. Conclusion: breastfeeding duration of 4-<6 months is associated with thinner IMT and thus has a protective effect on the development of cardiovascular disease. However the association with FMD in adolescence is less clear.